De pobladores a pobres. Representaciones documentales del colectivo Teleanálisis, durante la última fase de la dictadura militar en Chile - Francisco Núñez Capriles; Hernán Venegas Valdebenito (Les Cahiers ALHIM)
This article investigates the documentary series Teleanálisis and the way in which it represented the Chilean pobladores (shantytown dwellers) during the mass social and political protests and mobilizations between 1984 and 1989 which threatened the Chilean military dictatorship. In parallel to changes in the perspective of the opposition on how to defeat the dictatorship, the pobladores as a subject transformed, in the series' view, from an autonomous and central actor in the mobilizing strategy, to a second-order actor, without agency and subsumed into broader social categories.